Small molecule modulation of TrkB and TrkC neurotrophin receptors prevents cholinergic neuron atrophy in an Alzheimer's disease mouse model at an advanced pathological stage - Selena Gonzalez (Elsevier, 2022)
Degeneration of basal forebrain cholinergic neurons (BFCNs) in the nucleus basalis of Meynert (NBM) and vertical diagonal band (VDB) along with their connections is a key pathological event leading to memory impairment in Alzheimer's disease (AD). Aberrant neurotrophin signaling via Trks and the p75 neurotrophin receptor (p75NTR) contributes importantly to BFCN dystrophy. While NGF/TrkA signaling has received the most attention in this regard, TrkB and TrkC signaling also provide trophic support to BFCNs and these receptors may be well located to preserve BFCN connectivity. We previously identified a small molecule TrkB/TrkC ligand, LM22B-10, that promotes cell survival and neurite outgrowth in vitro and activates TrkB/TrkC signaling in the hippocampus of aged mice when given intranasally, but shows poor oral bioavailability. An LM22B-10 derivative, PTX-BD10–2, with improved oral bioavailability has been developed and this study examined its effects on BFCN atrophy in the hAPPLond/Swe (APPL/S) AD mouse model. Oral delivery of PTX-BD10–2 was started after appreciable amyloid and cholinergic pathology was present to parallel the clinical context, as most AD patients start treatment at advanced pathological stages. PTX-BD10–2 restored cholinergic neurite integrity in the NBM and VDB, and reduced NBM neuronal atrophy in symptomatic APPL/S mice. Dystrophy of cholinergic neurites in BF target regions, including the cortex, hippocampus, and amygdala, was also reduced with treatment. Finally, PTX-BD10–2 reduced NBM tau pathology and improved the survival of cholinergic neurons derived from human induced pluripotent stem cells (iPSCs) after amyloid-β exposure. These data provide evidence that targeting TrkB and TrkC signaling with PTX-BD10–2 may be an effective disease-modifying strategy for combating cholinergic dysfunction in AD. The potential for clinical translation is further supported by the compound's reduction of AD-related degenerative processes that have progressed beyond early stages and its neuroprotective effects in human iPSC-derived cholinergic neurons.